The World Experienced By The Mental Illness, A Joker (2019) Phenomenological Research - Fayyad, Muhammad; Ramadhan, Rafi Atha; Rahmawati, Kenfirda (Journal of English Education, Literature and Linguistics, 2023)
This study aims to determine the world experienced by the mentally ill Arthur Fleck of Joker (2019) through phenomenological analysis.This research uses qualitative methods. The authors chose this research based on the phenomenon of Joker related tothe joker's mental illness that contains experience of mental illness to various types ofmental health disorders. We felt excited because of the release of the Joker movie which raised the image of someone who is experiencing mental illness with various descriptions of interesting behaviors. The authors want to understand how the Joker handle the discrimination he experienced in this film. Then, The authors want to know more about the impact of the discrimination towards the Joker, and the factors as to why those who have mental illnesses frequently become a victim of discrimination. We believe that this will push people to be more sensitive, and value and understand the behaviors people may exhibit around them, and to understand the people who experience them and help them.These are why the authors are interested in conductinga study regarding the matter. The results of this research showed evidence of the Joker's methods of handling the negative experiences, the impacts and the factors of the said experiences and rejection in his social environment. Keywords: Phenomenology, Joker, Mental Illness.